i. (a + b)^{2 }= (-7 + 8)^{2 }

= 1^{2 }

= 1

a^{2 }+ 2ab + b^{2 }= (-7)^{2 }+ 2 x (-7) x 8 + 8^{2 }

= 49 – 112 + 64

= 1

∴(a + b)^{2 }= a^{2 } + 2ab + b^{2 }

(a – b)^{2 }= (-7 – 8)^{2 }

= (-15)^{2 }

= 225

a^{2 }– 2ab + b^{2 }= (-7)^{2 } – 2 x (-7) x 8 + (8)^{2 }

= 49 + 112 + 64

= 225

∴(a – b)^{2 }= a^{2 } – 2ab + b^{2 }

ii. (a + b)^{2 }= (11 + 3)^{2 }

= 14^{2 }

= 196

a^{2 }+ 2ab + b^{2 }= 11^{2 }+ 2 x 11 x 3 + 3^{2 }

= 121 + 66 + 9

= 196

∴(a + b)^{2 }= a^{2 }+ 2ab + b^{2 }

(a – b)^{2 }= (11 – 3)^{2 }= 8^{2 }

= 64

a^{2 }– 2ab + b^{2 }= 11^{2 }– 2 x 11 x 3 + 3^{2 }

= 121 – 66 + 9

= 64

∴(a – b)^{2 }= a^{2 } – 2ab + b^{2 }

iii. (a + b)^{2 }= (2.5 + 1.2)^{2 }

= 3.7^{2 }

= 13.69

a^{2 }+ 2ab + b^{2 }= (2.5)^{2 }+ 2 x 2.5 x 1.2 + (1.2)^{2 }

= 6.25 + 6 + 1.44

= 13.69

∴(a + b)^{2 } = a^{2 }+ 2ab + b^{2 }

(a – b)^{2 }= (2.5 – 1.2)^{2 }

= 1.32

= 1.69

a^{2 }– 2ab + b^{2 }= (2.5)^{2 }– 2 x 2.5 x 1.2 + (1.2)^{2 }

= 6.25 – 6 + 1.44

= 1.69

∴(a – b)^{2 }= a^{2 }– 2ab + b^{2 }